An atrioventricular septal defect with an Ebsteinoid right atrioventricular valve. (4th February 2022) - Hall, S; Deri, A; Delle Donne, MG
Abstract: Funding Acknowledgements: Type of funding sources: None. The combination of an atrioventricular septal defect (AVSD) with an Ebsteinoid atrioventricular valve is incredibly rare with only a handful of cases being described in the literature (1, 2). In this poster we describe the diagnosis of this anatomy in a neonate born at our centre. The baby was antenatally diagnosed with a chromosome 8p23.1 microdeletion which is associated with congenital heart disease and developmental delay (3). Although fetal echo had revealed a high suspicion of congenital heart disease, maternal BMI had prevented a precise diagnosis. The baby was born in good condition at thirty-nine weeks gestation weighing 2.4kg. She had been admitted to the neonatal unit where she was self-ventilating in room air with saturations above 90%. The echocardiogram was performed at one hour of age. The initial echo revealed a normal atrial arrangement with the heart in the left chest and the apex pointing to the left. There was normal pulmonary and systemic venous drainage. There was a complete AVSD with sizeable atrial and ventricular components. The left atrioventricular valve was dysplastic with at least moderate regurgitation. The right atrioventricular valve was displaced caudally and rotated into the right ventricular outflow tract. The right atrioventricular valve was also regurgitant. The right ventricle above the displaced atrioventricular valve was atrialized with the true right ventricle limited to the outlet portion. The great arteries were normally related. The ventricular component of the AVSD opened into the sub-pulmonary area along with two smaller muscular ventricular septal defects. These findings raised many clinical concerns including the insufficiency of the right ventricle to support a biventricular repair. Similarly, the severe left atrioventricular valve regurgitation precluded single ventricle palliative surgical techniques. After discussion between the multidisciplinary team and a second opinion sought from another centre, the family was counselled that this was a complex and life limiting form of congenital heart disease. Although surgical options were discussed with the family, the family opted for comfort care and the baby passed away at three weeks of age. Image 1: A complete AVSD with an Ebsteinoid right atrioventricular valve displaced caudally (a) resulting in an atrialized right ventricle (b). In addition, the left atrioventricular valve which straddles the ventricular septum is severely dysplastic (c) and regurgitant (d).